Bioavailability and Health Effects of Plastic Contaminants in Borehole Water Stored in Plastic Containers (Global Journal of Medical Research, 2016)
The aim of this study was to evaluate the bioavailability and health effects of plastic contaminants on borehole water stored in plastic containers. Three brands of plastic containers filled with borehole water were collected from homes in Ugbowo, Benin city. Physicochemical parameters were determined using standard methods. Total bacterial and coliform counts were determined using the pour plate technique. Conductivity, TDS, Chloride, Sulphate and Nitrate were within the recommended standards while turbidity and total iron were above recommended standards. The isolates identified include: Klebsiella sp, Bacillus sp, E. coli, Pseudomonas aeruginosa, Aspergillus flavus, Saccharomyces sp and Aspergillus niger. The total bacterial count in the water samples ranged from 1.4×10 3 cfu/ml to1.8×10 3 cfu/ml at week four while fungal counts was 1.3×10 2 cfu/ml to 1.6×10 2 cfu/ml. Bisphenol A was discovered to leach at detectable levels from the plastic containers as storage increased. The result of the BPA analysis revealed that BPA congeners ranged from 0.023mg/l within days of collection to 0.251ml/l at the fourth week of storage. This study has shown that storage of borehole water in plastic containers for prolonged period affects the bacteriological and chemical properties of the water, hence storage of borehole water in plastic for prolonged periods should be discouraged and discontinued.
Keywords: plastic contaminant; bioavailability; borehole water; bisphenol A